2005
DOI: 10.1038/sj.gene.6364186
|View full text |Cite
|
Sign up to set email alerts
|

Novel IL-6 haplotypes and disease association

Abstract: Interleukin-6 (IL-6) is a pleiotropic cytokine crucial in both adaptive and innate immunity. Numerous genetic studies have shown association with variants of this gene in a multitude of diseases and phenotypes. Most tests of association have focused on a limited set of promoter polymorphisms, in particular, the À174G4C; however, there are many inconsistencies within and between these studies. We propose that there is a more complex regulatory haplotype extending further upstream of the previously characterised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 21 publications
(25 reference statements)
2
36
1
Order By: Relevance
“…The inconsistency may reflect the disease-specific, tissue-specific and/ or environment-specific regulation of IL-6 expression. In addition, a recent study has suggested that the promoter haplotypes involving two other SNPs, -1363G/T and -1489CTdel affect the risk of systemic onset juvenile arthritis and these two polymorphisms, primarily -1363G/T, may further differentiate the effect of -174C/G although the functionality of these two SNPs remains to be determined (39). However, our data do not support the functional importance of the -1363G/T regarding the association with plasma IL-6 concentrations and lipid parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistency may reflect the disease-specific, tissue-specific and/ or environment-specific regulation of IL-6 expression. In addition, a recent study has suggested that the promoter haplotypes involving two other SNPs, -1363G/T and -1489CTdel affect the risk of systemic onset juvenile arthritis and these two polymorphisms, primarily -1363G/T, may further differentiate the effect of -174C/G although the functionality of these two SNPs remains to be determined (39). However, our data do not support the functional importance of the -1363G/T regarding the association with plasma IL-6 concentrations and lipid parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The Ϫ572GϾC SNP has also been associated with the plasma IL-6 concentration, with the rare C allele associated with higher IL-6 concentrations (15 ). A recent study also evaluated 2 other promoter variants, Ϫ1363GϾT and Ϫ1480CTdel, and although these variants were not shown to be functional, they did form a haplotype with the other promoter polymorphisms that showed an increased association with systemic-onset juvenile arthritis (16 ). This finding suggests the presence of functional polymorphisms at this locus that influence IL-6 concentration but that have yet to be identified.…”
Section: © 2008 American Association For Clinical Chemistrymentioning
confidence: 99%
“…A similar result has been shown in the study of Bennermo et al [9] , where healthy individuals homozygous for the G allele had a higher IL-6 response to vaccination with S. typhii as compared to individuals homozygous for the C allele. In addition to the above, there are four recently described SNP-s, -9316 T/C (rs1546762) obtained by searching the HapMap database [10] , -1363 G/T (associated with systemic onset juvenile arthritis [11] ), and +1753 C/G and +2954 G/C (incorporated into haplotypes associated with mortality in critically ill patients [12] ) also in the promoter and coding regions of IL-6. Not only the -174 polymorphism but also haplotypes may associate with the expression of IL-6.…”
Section: Cruited and Genotyped For Il-6 -174(g ] C) -9316(t ] C) -1mentioning
confidence: 99%